2017
DOI: 10.1126/science.aah5072
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic nerves activate an angio-metabolic switch in prostate cancer

Abstract: Nerves closely associate with blood vessels and help to pattern the vasculature during development. Recent work suggests that newly formed nerve fibers may regulate the tumor microenvironment, but their exact functions are unclear. Studying mouse models of prostate cancer, we show that endothelial β-adrenergic receptor signaling via adrenergic nerve-derived noradrenaline in the prostate stroma is critical for activation of an angiogenic switch that fuels exponential tumor growth. Mechanistically this occurs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
285
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(305 citation statements)
references
References 47 publications
(53 reference statements)
4
285
1
Order By: Relevance
“…PanINs), and thus cancer development in a susceptible host could be inhibited by ADRB2-antagonists. ADRB2 signaling likely promotes tumorigenesis through effects on both the epithelial and the stromal compartment (Hayakawa and Wang, 2017; Magnon et al, 2013; Zahalka et al, 2017). Although the effects of stress in promoting cancer have been linked in the past to suppression of the immune response (Partecke et al, 2016) or to recruitment of M2 macrophages (Madden et al, 2011; Pérez Piñero et al, 2012), we show here that many of the effects of circulating catecholamines are indeed direct, with stimulation of ADRB2-dependent pancreatic epithelial growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PanINs), and thus cancer development in a susceptible host could be inhibited by ADRB2-antagonists. ADRB2 signaling likely promotes tumorigenesis through effects on both the epithelial and the stromal compartment (Hayakawa and Wang, 2017; Magnon et al, 2013; Zahalka et al, 2017). Although the effects of stress in promoting cancer have been linked in the past to suppression of the immune response (Partecke et al, 2016) or to recruitment of M2 macrophages (Madden et al, 2011; Pérez Piñero et al, 2012), we show here that many of the effects of circulating catecholamines are indeed direct, with stimulation of ADRB2-dependent pancreatic epithelial growth.…”
Section: Discussionmentioning
confidence: 99%
“…While some of these stimulatory factors are likely provided by inflammatory leukocytes, the role of the nervous system in supporting tumor growth needs to be considered. Recent studies have shown the importance of the autonomic nervous system in tumorigenesis for prostate cancer (Magnon et al, 2013; Zahalka et al, 2017), ovarian cancer (Thaker et al, 2006), gastric cancer (Hayakawa et al, 2017; Zhao et al, 2014), and basal cell carcinoma (Peterson et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…; Zahalka et al. ). Although further studies are needed to elucidate the exact anti‐tumour mechanism, these findings suggest a potential role for β‐blockers in the treatment of cancer.…”
Section: Discussionmentioning
confidence: 97%
“…The sympathetic nerve system and specifically its neurotransmitter noradrenaline are known (1) to contribute to a favourable tumour microenvironment, for example by affecting stromal cells, endothelial cells, and tumour-associated macrophages (Magnon et al 2013), and (2) to stimulate tumour cell proliferation, via beta (b) adrenergic receptors on tumour cells (Coelho et al 2017). As since all of these processes are mediated via adrenergic receptors, the effects of b adrenergic blocking as a potential anti-tumour therapy have been investigated in in vitro, animal, and retrospective patient studies with promising results (Magnon et al 2013;Coelho et al 2017;Zahalka et al 2017). Although further studies are needed to elucidate the exact anti-tumour mechanism, these findings suggest a potential role for b-blockers in the treatment of cancer.…”
Section: Jongementioning
confidence: 99%
“…In addition to directly acting on tumour cells, β‐adrenoceptors play a major role in mediating the intimate crosstalk between tumour cells and their environment that has a profound influence on tumour growth and progression (Finotello and Eduati, ). In this respect, it has been demonstrated that propranolol counteracts the stress‐induced formation of new blood vessels in a mouse model of colorectal carcinoma and that the deletion of the gene encoding for β 2 ‐adrenoceptors leads to inhibition of angiogenesis in a mouse model of prostate cancer (Liu et al ., ; Zahalka et al ., ). In addition, propranolol prevents both macrophage recruitment into the tumour mass in a model of ovarian carcinoma and macrophage M2 polarization in a model of breast cancer (Armaiz‐Pena et al ., ; Qin et al ., ).…”
Section: Stress and β‐Adrenoceptor‐mediated Tumour Progressionmentioning
confidence: 97%